1994
DOI: 10.1007/bf01977670
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive disorder in children and adolescents. A 6-22-year follow-up study. Clinical descriptions of the course and continuity of obsessive-compulsive symptomatology

Abstract: Forty-seven individuals (28 male and 19 female) referred for treatment of obsessive-compulsive disorder (OCD) in childhood were followed-up 15 years later (range 6-22 years) in respect of psychiatric and personality disorders. In early adulthood, the patients could be sub-divided into 4 groups of about equal size. One group had no later OCD, another had OCD on a sub-clinical level, a third group had an episodic course of OCD, and a final group had a chronic and often very disabling OCD. Outcome was similar in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 39 publications
1
10
0
2
Order By: Relevance
“…AS has been associated with a host of comorbid conditions, including schizophrenia (Clarke,Little Johns, Corbett, & Joseph, 1989;Tantam, 1988), Tourette's syndrome (Kerbeshian & Burd, 1986), attentional, affective, and obsessional disorders (Ghaziuddin, Tsai, & Ghaziuddin, 1992b;Thomsen, 1994). More recent research has emphasized anxiety, mood and obsessional disorders to be particularly prevalent in this population (Green, Gilchrist, Burton, & Cox, 2000;Kim, Szatmari, Bryson, Streiner, & Wilson, 2000).…”
Section: Patterns Of Comorbiditymentioning
confidence: 94%
“…AS has been associated with a host of comorbid conditions, including schizophrenia (Clarke,Little Johns, Corbett, & Joseph, 1989;Tantam, 1988), Tourette's syndrome (Kerbeshian & Burd, 1986), attentional, affective, and obsessional disorders (Ghaziuddin, Tsai, & Ghaziuddin, 1992b;Thomsen, 1994). More recent research has emphasized anxiety, mood and obsessional disorders to be particularly prevalent in this population (Green, Gilchrist, Burton, & Cox, 2000;Kim, Szatmari, Bryson, Streiner, & Wilson, 2000).…”
Section: Patterns Of Comorbiditymentioning
confidence: 94%
“…Case studies have suggested potential links to other disorders including Tourette's syndrome (e.g., Gillberg and Rastam 1992;Kerbeshian and Burd 1986;Littlejohns et al 1990;Marriage et al 1993), obsessive-compulsive disorder (Thomsen 1994) and psychotic conditions (both psychotic depression and bipolar disorder) (Gillberg 1985). A small, mostly British literature suggests some increased risk for criminality and/or troubles with the law (e.g., Baron-Cohen 1988;Everall and LeCouteur 1990;Mawson et al 1985;Scragg and Shah 1994;Tantam 1988c;Wing 1981) although often legal troubles seem to stem from poor social judgment and limited empathy rather than malevolent intent (Ghaziuddin et al 1991;Klin et al 2004).…”
Section: Co-morbiditymentioning
confidence: 98%
“…OCD is in many cases a chronic illness with``ups and downs'' over time (16,8). Therefore, we can not exclude the idea that there may be a``time eect'' in the patients, that augmentation therapy was introduced at a point when the clinical status was poor, and that the clinical observations may re¯ect¯uctuations over time.…”
Section: Discussionmentioning
confidence: 97%